Randomized, placebo-controlled study of the efficacy of a calcium phosphate containing paste on dentin hypersensitivity. Issue 11 (November 2015) - Mehta, Deepak; Gowda, Vishwas; Finger, Werner J.; Sasaki, Keiichi
Abstract: Objective: Hypersensitivity of non-carious cervical lesions (DH) is a frequently encountered disease. This randomized, controlled, single-blind crossover study evaluated the effectiveness of a calcium phosphate containing desensitizer paste (TAP) on DH in comparison to water as placebo (PLA). Methods: In this clinical trial 35 patients were randomly assigned to the test and the negative control group. Using a 10 cm long VAS (visual analog scale) patients should respond with DH score >6 on one tooth in each of two quadrants for allocation. Pain stimuli were a 2-seconds air blast (AB) and probe scratching (PS) of the exposed dentin. VAS scores were determined pre-operatively (PRE), immediately after treatment (POST), at 1 week, 1, 3 and finally after 6 months. Results: Both TAP and PLA applications decreased DH significantly at POST and throughout the 6-months recalls ( p  < 0.001). Pain reductions upon AB stimulation of TAP treated teeth, assessed at POST and 6 months were 35 and 55%, upon PS stimuli 21 and 54%, respectively. PLA treated lesions responded to AB at POST and after 6 months with 20 and 36% pain reduction, to PS with 11 and 30% pain reduction, respectively. Differences between TAP and PLA pain scores were statistically significant at all recalls ( p  < 0.05). Significance: TAP paste reduced DH successfully during this 6-months trial. The calcium phosphate crystallites included in the paste and the presumed hydroxyapatite precipitates upon exposure to saliva were hypothetically able to occlude open dentinal tubules, at least to some extent. TAP is considered a biocompatible desensitizer paste.